MHD Pulsating forced convection of nanofluid over parallel plates with blocks in a channel - Selimefendigil, Fatih; Öztop, Hakan Fehmi (Pergamon-Elsevier Science Ltd, 2019)
Forced convection of pulsating nanofluid flow over corrugated parallel plate in the presence of inclined magnetic field is numerically studied by using Galerkin weighted residual finite element method. Impacts of Reynolds number (between 100 and 500), Hartmann number (between 0 and 15), magnetic inclination angle (between 0 degrees and 90 degrees), number (between 1 and 12) of corrugation wave, height (between 0.05h and 0.35h) of the corrugation wave, solid particle volume fraction (between 0% and 4%), pulsation amplitude (between 0 and 0.9) and frequency (Strouhal number between 0.25 and 2) on the convective heat transfer features are analyzed. It is observed that increasing the Reynolds number, Hartmann number, magnetic inclination angle and solid particle volume fraction of the nanoparticle results in heat transfer enhancement while corrugation wave parameters have reverse impact on heat transfer enhancement in steady flow case. Various blocks of the heated plate contribute differently to the overall heat transfer rate and influence of block height on the distribution of the contributed effects is remarkable. Magnetic field redistribute the vortices between heated blocks of the corrugated plate and enhance the heat transfer both in steady flow and pulsating flow. Values for the spatial average Nusselt number are higher in pulsating flow as compared to steady case. At pulsation amplitude of 0.9, 40.30% and 34% heat transfer enhancement are obtained as compared to steady case in the absence and presence of magnetic field at Hartmann number of 15. Including nanoparticles in pulsating flow shifts the spatial average Nusselt number plots as compared to base fluid. The values at the highest particle volume fraction are higher 15-16% in pulsating flow as compared to base fluid and they are slightly different than the ones obtained in the steady flow.
Keywords: Pulsating flow; Corrugation; Finite element method; MHD flow